Pegaspargase, venetoclax, and nelarabine: A successful bridge to allogeneic hematopoietic stem cell transplantation in a relapsed/refractory T-cell acute lymphoblastic leukemia patient - Yiğit Kaya, Süreyya; Bektaş, Şebnem; Aşkın, Abdullah Emre; Balık Aydın, Berrin; Mutlu, Yaşa Gül; Sevindik, Ömür Gökmen (Springer, 2023)
[Abstract Not Available]
Keywords: Pegaspargase; Hematopoietic Stem Cell; Venetoclax